Wohnungsgenossenschaften: bezahlbare Mieten in angespannten Märkten - Tobias Wolbring; Matthias Wrede (Wirtschaftsdienst, 2024)
What can be done about the significant increase in rents on the tight housing markets in Germany? One way is to better support housing cooperatives. The analysis of surveys among housing cooperatives and the 2011 and 2022 census show that although housing cooperatives are also significantly affected by general market trends such as rising costs, they do not exploit their power in tight markets in the same way as other housing providers.
Keywords: P13; R31; 330